Desarrollo del arco dentario superior deciduo y su relación con el tipo de lactancia recibida en niños de 5 años de edad, de la Escuela de Educación Básica Teniente Hugo Ortiz, periodo octubre 2018-febrero 2019 - Granda Granda, Elena Samantha (2019)
The present investigation was of observational, analytical and transversal type, the objective was to relate the type of lactation and the development of the deciduous upper dental arch, in children of 5 years of age of the School of Basic Education “Teniente Hugo Ortiz”. For this, 50 children were evaluated using diagnostic models, the data was recorded in an observation form, and a survey was applied to parents about the type and duration of breastfeeding that the children received. The results showed that the most frequent lactation type was the mixed lactation with a percentage of 36% of the sample, the predominant arch shape was ovoid with 56%, the average length of the arch was 30.22mm and the perimeter reached an average of 69.94mm, the intercanine width obtained an average of 31.69mm, the intermolar width was 39.33mm and the palatal height obtained an average of 15.43mm. The results indicate that in exclusive breastfeeding, the intermolar width shows a statistically significant difference (p = 0.051), while in the inter-canine width (p = 0.061) it is considered significant, especially due to the decrease in measurements between those who breastfeeding in a period of 4 to 6 months (28.84mm) and those who received in a period greater than 6 months (32.27mm); mixed lactation showed significant statistical difference in palatal height (p = 0.030); As for artificial lactation, it was not possible to verify an existing statistical relationship with the development of the deciduous upper dental arch. Keywords: Breastfeeding, Dimensions, Dental arch, Tooth deciduous